Retroperitoneal Mystery: Primary Retroperitoneal Mucinous Cystic Neoplasm With Concomitant Cystic Neoplasm of the Pancreas - Luis Gonzalez Miranda; Jessica Qiu; Yubo Wu; Kirsten Greene (Case Reports in Urology)
Urologists are commonly referred patients with retroperitoneal lesions and masses arising from or involving the kidney. In this case, the patient had a retroperitoneal mass identified on imaging which was initially concerning for a cystic renal neoplasm, but it was clearly distinct from all surrounding structures. Pathology found the very uncommon and unexpected diagnosis of a mucinous cystic neoplasm (MCN) with ovarian-type stroma suspected to have arisen from the pancreas. MCNs are lesions that most commonly arise in the ovaries, but less often can arise in extraovarian tissues. Of these extraovarian MCNs, primary retroperitoneal MCNs are exceedingly rare masses with some similarity to their pancreatic and ovarian counterparts. We present a case of an MCN found in the retroperitoneum and initially mistaken for a cystic renal mass, with histological markers and a concomitant pancreatic cyst that suggests possible pancreatic origin. Interestingly, no literature has described pancreatic MCNs without invasive features that have been found in the retroperitoneum without any formal tissue connection to the pancreas. The pathogenesis of retroperitoneal MCNs is still unknown, and as a result, the optimal treatment strategy is unclear.